Carbon Dioxide Activated SiC-CDC: Attractive Material for Supercapacitor Electrodes. (8th December 2015) - Jänes, Alar; Tee, Ester; Tallo, Indrek; Thomberg, Thomas; Lust, Enn
Abstract : Carbide-derived carbons (CDCs) were synthesized from SiC powders (SiC-CDC) via gas phase chlorination within the temperature range from 1000 ºC to 1100 ºC. Thereafter the CDCs were additionally activated by CO2 treatment method, resulting in nearly two-fold increase in specific surface area. The low-temperature nitrogen sorption experiments were performed and the specific surface areas from 1100 m 2 g -1 up to 2270 m 2 g -1 were obtained, depending on the extent of CO2 activation. The energy and power density characteristics of the supercapacitors based on 1 M (C2 H5 )3 CH3 NBF4 solution in acetonitrile and SiC-CDC as an electrode material were investigated using the cyclic voltammetry, electrochemical impedance spectroscopy, galvanostatic charge/discharge and constant power discharge methods. The electrochemical data indicated two-times increase in specific capacitance. The activation of SiC-CDC with CO2 significantly increases (more than 40%) the performance of the supercapacitors, especially at higher potential scan rates and at higher power loads.